2016
DOI: 10.1177/0886260516651314
|View full text |Cite
|
Sign up to set email alerts
|

Attachment Anxiety as a Risk Factor for Subsequent Intimate Partner Violence Victimization: A 6-Month Prospective Study Among College Women

Abstract: Recent research suggests that individuals with attachment difficulties are at increased risk for experiencing intimate partner violence (IPV) victimization. However, most studies conducted on this topic have been cross-sectional, leaving it unclear whether attachment difficulties actually precede this type of violence. The current 6-month prospective study examined the relation between adult attachment and subsequent IPV victimization in a sample of 133 college women. At Time 1, participants completed the Expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 37 publications
0
17
0
3
Order By: Relevance
“…For example, several studies tested this relationship considering the role of early trauma. First, results brought by Sandberg et al ( 2016 ) underlined that anxious attachment significantly predicted physical IPV victimization also after controlling the role of trauma. In contrast, Karakoç et al ( 2015 ) showed that, when controlling for the effect of trauma, insecure attachment no longer predicted IPV victimization among patients suffering from depression.…”
Section: Resultsmentioning
confidence: 98%
“…For example, several studies tested this relationship considering the role of early trauma. First, results brought by Sandberg et al ( 2016 ) underlined that anxious attachment significantly predicted physical IPV victimization also after controlling the role of trauma. In contrast, Karakoç et al ( 2015 ) showed that, when controlling for the effect of trauma, insecure attachment no longer predicted IPV victimization among patients suffering from depression.…”
Section: Resultsmentioning
confidence: 98%
“…A recent longitudinal study reported that attachment anxiety was associated with increased risk for experiencing physical assault, while attachment avoidance was unrelated to subsequent IPV victimization ( Sandberg et al, 2019 ). To measure causality one must have a prospective design.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, Furman and Simon [ 37 ] note that men tend to show greater avoidant attachment and lesser anxious attachment. Likewise, the anxious attachment that some women have has been related to greater victimization [ 38 ]. However, other authors have related victimization to aspects that are more interconnected with the role that society gives to men and women.…”
Section: Discussionmentioning
confidence: 99%